2005
DOI: 10.1063/1.1919393
|View full text |Cite
|
Sign up to set email alerts
|

Surface-charge lithography for GaN microstructuring based on photoelectrochemical etching techniques

Abstract: Cathodoluminescence microscopy and spectroscopy of GaN epilayers microstructured using surface charge lithography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…These nanocolumns represent whiskers related to threading dislocations. As it was shown previously [10,13], threading dislocations in GaN are negatively charged and, under relevant conditions, this charge makes them resistant to PEC etching. The results of technological exploration demonstrate the validity of the proposed technological route.…”
Section: Resultsmentioning
confidence: 51%
“…These nanocolumns represent whiskers related to threading dislocations. As it was shown previously [10,13], threading dislocations in GaN are negatively charged and, under relevant conditions, this charge makes them resistant to PEC etching. The results of technological exploration demonstrate the validity of the proposed technological route.…”
Section: Resultsmentioning
confidence: 51%
“…9 We have previously shown that SCL followed by PEC etching enables the controlled production of ultra thin continuous suspended membranes of GaN. 5, 10 We have recently extended this method to allow for the controlled fabrication of suspended ultra-thin GaN membranes of predetermined dimensions with supporting structures. 6 SCL is a maskless approach, which involves direct writing on the sample surface by low-energy ions.…”
Section: Methodsmentioning
confidence: 99%
“…Another approach for manufacturing nanostructured GaN membranes is based on the so-called surface charge lithography (SCL) [31], which implies low-dose low-energy ion-beam treatment of the GaN surface followed by closed-circuit photoelectrochemical (PEC) etching in aqueous solution of KOH under UV excitation. Low-dose low-energy ion-beam treatment induces a negative charge on the semiconductor surface, which shields the material against subsequent PEC etching.…”
Section: Technologies Applied For the Fabrication Of Gan Membrane Strmentioning
confidence: 99%